Measuring Oral Health: From Simple Scoring to a Combined Risk-assessment Approach. (2nd November 2020) - Burke, FJ Trevor; Chapple, Liz; Busby, M
Abstract : The ability to measure oral health is central to successful, patient-oriented clinical practice. In this regard, there have been a variety of definitions of oral health over the years, with the most recent being one by the FDI. Specific quality measures have been designed to assess, for example, the technical excellence of restorations, periodontal health, tooth wear, and, depth of caries (e.g. ICDAS). However, a single index that would produce a composite score of oral health could be considered desirable and the ideal criteria for this are discussed, namely, that it should be reproducible and valid, readily understood and capable of being used by dentists with minimal instruction and training. The profession has now entered the era of personalised medicine where risk factors need to be identified and patients educated about these, thus empowering them to work with their care provider and at home to take responsibility for their own dental health. As a result, a variety of oral health assessments, which include assessments of risk factors, have now become available: examples of these are described, with suggestions regarding the implementation of such into a clinician's practice being given. CPD/Clinical Relevance: The ability to measure oral health is central to successful clinical practice.